If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+(x+4)-(x-2)=4
We simplify the equation to the form, which is simple to understand
x+(x+4)-(x-2)=4
Remove unnecessary parentheses
+x+x+4-(+x-2+)=+4
Remove unnecessary parentheses
xx+4-1x+2=4
We move all terms containing x to the left and all other terms to the right.
+1x+1x-1x=+4-4-2
We simplify left and right side of the equation.
+1x=-2
We divide both sides of the equation by 1 to get x.
x=-2
| 4(x+3)=5x+9 | | -3w+3=2(w-6) | | (X-3)+(X-1)=(6X+1X) | | 6[x-(2-3x)+1]=4x-6 | | 37.1=p*4.823 | | 2c^2-16=0 | | 4.823=p*37.1 | | -2x^2+6x+20=0 | | X=(X-2)+1 | | 5(x-3)-2x=-30 | | 2(1-X)=7-X | | 15t=360 | | 2x+10-3=-2x-1+1 | | 1c^2-3c=0 | | 7+3w=1 | | 16x=9x+5 | | 3(2x-4)-2x=24 | | 7w-5=-8w+12 | | 2X^2-3=9X-13 | | 4x*4x+12x=0 | | 25x^5-10x^3+1=0 | | 6w=78 | | -3x^2-10x-13=0 | | 286=26m | | 2x+.75(4x+16)=7 | | -8(-21)= | | S^5-14s^4+40s^3= | | 4x+12x=4 | | w=0.35*56 | | 84=6p | | .35*w=56 | | -7-(12)= |